Correlation between fall risk increasing drugs (FRIDs) and fall events at a rehabilitation hospital - Castaldi, Silvana; Principi, Niccolò; Carnevali, Davide; Tiwana, Navpreet; Pietronigro, Anna; Mosillo, Marco; Marrazzo, Matteo; Colombo, Roberto; Avanzi, Gianluca Maria; Corna, Stefano (Acta Biomedica Atenei Parmensis, 2022)
Background and aimFalls and fall-related injuries are a major public health issue which needs global attention due to its clinical and socioeconomic impact. Important risk factors for falls are polypharmacy and the assumption of so-called Fall Risk Increasing Drugs (FRIDs). Aims of our study were to investigate the associations between falls and the use of medications among inpatients by conducting a retrospective case-control study in a rehabilitation hospital in Northern Italy in 2018.MethodsA Conditional Logistic Regression was performed to analyze the impact that 13 types of FRIDs individually and the number of administrated FRIDs had on the risk of falling. A second regression model was obtained adjusting the case-control matching for CIRS, Morse and Barthel scores.ResultsWe identified 148 cases and 444 controls. 3 types of FRIDs were significantly correlated (p < 0,05) with an increased risk of falling: Antipsychotics, Antidepressants, Diuretics.Antidepressants were the only type of FRID significantly correlated (p=0,008) even in the model adjusted for CIRS, Morse and Barthel scores.The unadjusted model showed that the addition of one type of FRID to therapy was significantly associated with the fall event (p